Diseño de un protocolo de telegenética como asistencia al proceso de diagnóstico y registro de los recién nacidos con anomalías congénitas en las regiones de Los Lagos y de Arica y Parinacota - Castillo T., Silvia; Pardo V, Andrea (Revista Hospital Clínico Universidad de Chile, 2019)
The majority of clinical geneticists in Chile work in the Metropolitan Region (78%). To expand the area of Telemedicine and support the management of the Ministry of Health, we present this Telegenetics development project that includes innovation of assistance and educational nature directed to regions. The implementation of the National Registry of Congenital Anomalies in Chile (RENACH) in the public and private systems, in December 2015, and the obligation to record and describe the anomalies in all newborns, constitutes a favorable scenario that would benefit from the support of clinical geneticists. This proposal brings together a team of 18 specialists and 6 fellows, professionals from different Universities and / or Hospitals of Health Services, in a collaborative project in the area of clinical genetics, which, supported by the HCUCH + CIMT Telemedicine project, will contribute to two regions of Chile better tools for the diagnosis and comprehensive management of newborn patients with congenital anomalies. It can serve as a pilot for a new way to support the registration of malformations throughout Chile and teach clinical genetics concepts. The expected benefits are to improve the quality of care and health management in patients with little-known diseases.